"Anything that makes life's journey better." Exploring the use of digital technology by people living with motor neurone disease. Issue 5 (3rd July 2017) - Hobson, Esther V.; Fazal, Saima; Shaw, Pamela J; McDermott, Christopher J
Abstract: Our aim was to explore the attitudes of those living with motor neuron disease towards digital technology. Postal and online questionnaires surveyed 83 people with MND (pwMND) and 54 friends and family members (fMND). Five pwMND and five fMND underwent semi-structured interviews. 82% of pwMND and 87% of fMND use technology every day with iPads and laptops being the devices most commonly used. pwMND used technology to help them continue to participate in everyday activities such as socialising, entertainment and accessing the internet. The internet provided peer support and information about MND but information could be distressing or unreliable. Participants preferred information from professionals and official organisations. Participants were generally supportive of using of technology to access medical care. Barriers to technology, such as lack of digital literacy skills and upper limb dysfunction, and potential solutions were identified. More challenging barriers included language and cognitive difficulties, and the fear of becoming dependent on technology. Addressing the barriers identified in this research could help pwMND access technology. However, as healthcare delivery becomes more reliant on digital technology, care should be taken to ensure that those who are unable or unwilling to use technology continue to have their needs met in alternative ways.